Factors influencing consumer loyalty: evidence from the Ghanaian retail banking industry - Omoregie, O.K.; Addae, J.A.; Coffie, S.; Ampong, G.O.A.; Ofori, K.S. (International Journal of Bank Marketing, 2019)
Purpose The increasing number of banks in the Ghanaian banking industry has brought about intense competition in the industry. The purpose of this paper is, therefore, to examine the factors that influence retail banking customers’ loyalty intentions. Design/methodology/approach In order to validate the proposed research model, the study adopts a survey design. Data were collected from 565 customers of the top performing banks in terms of customer deposits. Data analysis employed the partial least squares structural equation modeling (PLS–SEM) using SmartPLS version 3. Findings Results from the PLS–SEM analysis indicated that satisfaction, service quality and trust had significant effect on loyalty, with satisfaction having the most significant effect. Interestingly corporate image was found to have a significant effect on both satisfaction and trust but not on loyalty. In all, the proposed model accounted for 63.3 percent of the variation in loyalty. Research limitations/implications The current study samples customers from only the top performing banks in Ghana. The use of cross-sectional data makes it impossible to study how customers’ perceptions change over time. Results from this study could, however, help managers of banks in designing strategies aimed at improving customer loyalty in order to consolidate their market share. Originality/value This paper adds to existing works that focus on loyalty in the retail banking sector, especially from the context of a developing economy. The study draws attention to the interrelationship among service quality, perceived value, satisfaction, image, trust and loyalty.
Keywords: Service quality; Corporate image; Loyalty; Structural equation modelling; Customer satisfaction; Trust